Preoperative Embolization of Fisch Grades II–IVa Juvenile Nasopharyngeal Angiofibromas: Transarterial Embolization in the Age of Onyx - Vakharia, Kunal (Cureus, 2021)
Objective The current mainstay treatment for juvenile nasopharyngeal angiofibromas (JNAs) is surgical resection, but embolization of primary feeding arteries through endovascular transarterial and direct tumoral puncture embolizations with various agents has been described. We describe a single institutional experience with JNA embolization utilizing Onyx (Medtronic, Dublin, Ireland). Methods A retrospective records review was performed to identify patients who underwent embolization for devascularization of Fisch grades II-IVa JNA (tumor extension beyond the sphenopalatine region) before surgical resection between 2010 and 2019. Fluoroscopy time, grade, intraoperative blood loss, and clinical follow-up data were compiled. Tumor devascularization percentage was calculated using ImageJ software (public domain, BSD-2) by measuring the ratio of preoperative and postoperative embolization tracing. Results Five consecutive patients (ages 12-16 years [average 14 years]; all male) with JNAs underwent preoperative transarterial embolizations performed under general anesthesia. All patients presented with epistaxis; two also presented with headaches. Fisch grades were II in two patients, IIIa in two, and IVa in one. The patient with the grade IVa lesion underwent direct transtumoral puncture and Onyx embolization. The mean percentage of all tumor devascularizations postembolization was 86.0±9.7%.Complete resection 24-48 hours postembolization was obtained for grades II and IIIa lesions with <700 mL blood loss. No embolization-related complications and no clinical sequelae were present in the five cases after embolization. Conclusion In our experience, Onyx embolization of JNAs was safely conducted with adequate tumor penetration beyond the sphenopalatine region through transarterial routes.